Psychiatric Impact of Infertility and Assisted Reproductive Technologies A Prospective Study (Medical Forum Monthly, 2024)
Objective: The purpose of this research would be to explore the psychological effects of infertility and ART treatment as experienced by patients who received such treatments.Study Design: A Prospective Study.Place and Duration of Study: This study was conducted at the Department of Psychiatry & GYNAE & OBS department Mardan Medical Complex (MMC) Mardan, Khyber Pakhtunkhwa Pakistan from 2nd February 2021 to 3rd August 2021.Methods: A total of 98 respondents in the study consisted of infertile patients who underwent evaluation and treatment. Patients who met the criteria were included; Aged between 20 and 45 years, Diagnosis of infertility based on the WHO definition meaning failure to conceive for 12 months of engaging in unprotected intercourse, and Giving informed consent to participate in the study.Results: This study was conducted among 98 participants where 60 of the participants were female (61.2%) while 38 were male (38.8%). The mean age of participants was found to be 34.5±4.2 years. The average duration of infertility was 4.1±2.3 years. The mid-treatment phase’s average BDI score increased from 14.5 ±7.6 The median age ranged at baseline to 42.3±9.7, indicating a significant rise in depressive symptoms (p<0.05). Conclusion: Infertility and ART are correlated with high levels of psychiatric disturbance – with more focus on depression and anxiety. The fact that depressive symptoms can remain a problem even after the end of IVF treatment underscores the necessity of mental health assessment in infertility